2011
DOI: 10.1115/1.4004410
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stents and Flow Diverters on Hemodynamics in Idealized Aneurysm Models

Abstract: Cerebral aneurysms constitute a major medical challenge as treatment options are limited and often associated with high risks. Statistically, up to 3% of patients with a brain aneurysm may suffer from bleeding for each year of life. Eight percent of all strokes are caused by ruptured aneurysms. In order to prevent this rupture, endovascular stenting using so called flow diverters is increasingly being regarded as an alternative to the established coil occlusion method in minimally invasive treatment. Covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 22 publications
5
66
0
Order By: Relevance
“…Streamlines are employed for comparing flow patterns. They are often seeded on the ostium and displayed side-by-side [2], [6], [16]. However, either the entire set of lines is displayed leading to visual clutter or representative lines must be selected manually.…”
Section: Virtual Stentingmentioning
confidence: 99%
“…Streamlines are employed for comparing flow patterns. They are often seeded on the ostium and displayed side-by-side [2], [6], [16]. However, either the entire set of lines is displayed leading to visual clutter or representative lines must be selected manually.…”
Section: Virtual Stentingmentioning
confidence: 99%
“…In a computational fluid dynamic study performed by Seshadhri and colleagues [28], the hemodynamic effects of the flow-diverting stents were analyzed, taking into account the morphologic characters of the aneurysm. The investigators found that the "dome to neck ratio (D/N ratio)" was crucial in determining the flow-modulating effect of the porous stents (Fig 5).…”
Section: Commentmentioning
confidence: 99%
“…Additionally, the flow stasis within the aneurysm has been computed from the turnover time [22,36] and is shown in Table 2 as well. This turnover time is determined by dividing the full aneurysm volume by the inlet volume flow rate found at the aneurysm neck, defined as a straight plane placed directly above the stent.…”
Section: Resultsmentioning
confidence: 99%